2005
DOI: 10.1007/s00268-004-7576-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation: Not a Clinically Relevant Phenomenon in Colorectal Cancer

Abstract: The aim of this study was to identify the risk factors for bacterial translocation and to determine the clinical significance of bacterial translocation in patients with colorectal cancer. Mesenteric lymph node sampling was performed to identify the presence of bacterial translocation in 75 patients with colorectal cancer undergoing laparotomy. Bacterial translocation was identified in 29 patients (39%), with the most common organism being Escherichia coli (31%). Three factors for bacterial translocation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…BT occurred more frequently in patients who underwent emergency surgery and in those who received preoperative TPN. In contrast to reports published previously by both the authors and other investigators, there was no evidence to suggest an independent association between BT and age 8 , intestinal obstruction 3,11 , obstructive jaundice 6,12 , inflammatory bowel disease 13 or malignancy 14 . The reason for these differences is almost certainly a consequence of the fact that all previous studies based their conclusions exclusively on univariate analysis.…”
Section: Discussionmentioning
confidence: 80%
“…BT occurred more frequently in patients who underwent emergency surgery and in those who received preoperative TPN. In contrast to reports published previously by both the authors and other investigators, there was no evidence to suggest an independent association between BT and age 8 , intestinal obstruction 3,11 , obstructive jaundice 6,12 , inflammatory bowel disease 13 or malignancy 14 . The reason for these differences is almost certainly a consequence of the fact that all previous studies based their conclusions exclusively on univariate analysis.…”
Section: Discussionmentioning
confidence: 80%
“…The increased level of antibodies in benign diseases may be related to bacterial translocation (BT). BT frequently occurs in patients with benign and malignant gastrointestinal diseases 2, 3 and may be one of the reason of an augmented immune response. In colorectal cancer patients, BT in the mesenteric lymph nodes is indicative of a worse outcome 38.…”
Section: Discussionmentioning
confidence: 99%
“…In different pathologies of the digestive tract, including cancer, the altered colonization and bacterial translocation occurr 1-3 that may change the pattern and level of circulating anti-carbohydrate antibodies. Comparative data about spontaneously occurring anti-carbohydrate antibodies in relation to survival of patients with gastrointestinal cancer are scanty, but may be of clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…12 Multiple reviews of the literature have concluded that BT occurs in humans, although its clinical significance has been questioned. 11,13-16 BT has been studied or described in humans in many varied clinical scenarios such as laparotomy, 17,18 emergency and elective surgery, [17][18][19][20] hematologic and colorectal malignancies, 21,22 intestinal obstruction, 23,24 burns, 25 inflammatory bowel disease, 26,27 aortic aneurysm repair, 28 liver resection, 29,30 obstructive jaundice, 31,32 trauma, [33][34][35] pediatric small bowel transplant, 36 and surgical neonates and infants receiving PN, 37 among others. Several of these studies also related BT to increased morbidity, [17][18][19]21,[23][24][25][26]28,29,31,33,34,37 but others did not.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies also related BT to increased morbidity, [17][18][19]21,[23][24][25][26]28,29,31,33,34,37 but others did not. 20,22,27,30,32,35,36 A commonly proposed promotional mechanism of BT is physical damage to the barrier function of the intestinal mucosa leading to increased permeability. 13,15,38 A stercoral injury resulting from our patient' s chronic fecal impaction could cause such damage directly, although such injuries are rare and typically seen in elderly, nursing home-dependent, bedridden, or narcotic-dependent patients.…”
Section: Discussionmentioning
confidence: 99%